Fiscal Policy Led by Tax Incentives: Croatian Experiences - Bogovac, Jasna; Hodžić, Sabina (Naše gospodarstvo/Our economy, 2014)
Multinational enterprises play an important role in the field of foreign direct inve- stment activity. However, investments that are desirable from the standpoint of the host country might be rejected by the strategic management of multinational enter- prises due to other, more important aspects of the tax system, such as tax risks. This paper examines how important tax incentives are for Croatian multinational enter- prises as a fiscal instrument for attracting foreign direct investment. We found that tax incentives play an important role during the strategic decision-making process of multinational enterprises, in which the decisive factors are unpredictable tax risks and costs
Keywords: multinational enterprises; foreign direct investment; tax incentives